Teacher’s Role In Applying Of Assertive Discipline To Student At MAN 1 Solok Selatan - Ananda, Intan Tria; Elmiati, Elmiati; Putri, Dian Mega (JUPE : Jurnal Pendidikan Mandala, 2023)
Abstrak. The purpose of this research is to find out the role of teachers in implementing assertive discipline in senior high school students. The implementation of this research is to find information about how the role of teachers in applying assertive discipline in managing the classroom in English learning. Furthermore, this research is a descriptive research and the data were obtained from 2 English teachers in Man 1 Solok Selatan. To collect data, the researcher used observation checklist, and field notes, as instruments in this study. Based on the results of data analysis, the researcher concluded that English teachers who teach in classes X and XI, Man 1 Solok Selatan apply assertive discipline well, as evidenced by the existence of reference indicators about the role of teachers in applying assertive discipline. Teachers who teach English in classes X and XI, have fulfilled 14 sub indicators.